Using imaging to combat a pandemic: rationale for developing the UK National COVID-19 Chest Imaging Database. Issue 2 (13th August 2020) - Jacob, Joseph; Alexander, Daniel; Baillie, J. Kenneth; Berka, Rosalind; Bertolli, Ottavia; Blackwood, James; Buchan, Iain; Bloomfield, Claire; Cushnan, Dominic; Docherty, Annemarie; Edey, Anthony; Favaro, Alberto; et al.
The National COVID-19 Chest Imaging Database (NCCID) is a repository of chest radiographs, CT and MRI images and clinical data from COVID-19 patients across the UK, to support research and development of AI technology and give insight into COVID-19 disease https://bit.ly/3eQeuha